Thermal Stability Test and Formulation of Sodium Lignosulfonate with Isoamyl Alcohol as EOR Surfactant - Andriani, Anisa Novi; Azis, Muhammad Mufti; Purwono, Suryo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Sodium lignosulfonate (SLS) is a promising low-cost surfactant that can be prepared from biomass. There has been large interest to utilize SLS as a chemical Enhanced Oil Recovery (EOR) surfactant. For that purpose, SLS is often mixed with other chemicals such as alcohols. The aim of this study was to find the best formulation of mixed-surfactant and to perform its thermal stability. The resulting mixed-surfactant was then characterized with variety of tests: aqueous stability, phase behavior, and IFT values. We found that a mixture that consists of 50 wt.% SLS, 30 wt.% Isoamyl Alcohol, and 20 wt.% of Palm Fatty Acid Distillate (PFAD) soap gave ultralow IFT at 1.864 × 10-3 mN/m. Phase behavior test shows that 1 wt% of mixed-surfactant formed a Winsor Type III. Subsequently, thermal stability test was conducted at 70°C for 90 days. The results showed that the IFT value fluctuates within the range of 10-3 mN/m for the first three weeks. After three weeks, the IFT values tend to increase to 10-2 mN/m until the end of the test. Hence, although ultralow IFT was achieved in the beginning of the test, further study is needed to improve the long-term stability of the present mixed-surfactant